IMPLEMENTASI PEDULI LINGKUNGAN PADA SEKOLAH ADIWIYATA DI SD NEGERI JETAK GODEAN SLEMAN - Susanti, Almira Dwi (Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas PGRI Yogyakarta, 2021)
ABSTRACTThis study aims to determine the implementation of environmental care at Adiwiyata schools in the implementation of self-development programs, integration with subjects, and school culture at SD N Jetak Godean, Sleman.This study used a qualitative method. Data collection techniques were in the form of interviews and documentation. Sources of data obtained from school principals, teachers and students as research subjects. The data analysis technique used the Model Miles and Huberman which includes data collection, data reduction, data presentation and conclusions. Check the validity of the data used source and technical triangulation.The results of the study can be concluded that the implementation of environmental care at Adiwiyata schools at SD N Jetak Godean included: 1) Self- development programs, namely taking care of plants, gardens, â€œThursday Pahingâ€ activities, giving advice and being responsible when violating the rules and regulations, giving ceremonial mandates regarding 19 PHBS skill and Adiwiyata characters, providing of hand washing facilities, and honesty canteen. 2) The integration of subjects at SD Negeri Jetak had used the 2013 Adiwiyata-based curriculum, the preparation of indicators was made more specific, such as observing sprouts, developing participatory Â and Â educative Â activities,Â the Â environment Â wasÂ used Â as Â a Â learning Â resource Â and media, Â study tours, conveying the importance of caring for the environment 3) School culture at SD Negeri Jetak included making composter, biopori, hydroponics, extracurricular and competitions, inviting students to pick up trash, watering, giving words of praise as a reward, cleaning the school environment as a sanction, unless accidentally, communicating the school's vision and mission .Â Keywords: Character, Education, Environmental Care